Relational Justice in Qur’anic Inheritance: A Maqāṣidī–Reciprocal Reinterpretation of QS. An-Nisā’ (4):11–12 through the Basuluh Tradition of the Banjar Community - Fiddian Khairudin; Masduki Masduki; Muh Said HM; Siti Marpuah (Jurnal Ushuluddin, 2025)
This article examines the reinterpretation of Qur’anic inheritance norms through the lens of relational justice by engaging with the basuluh tradition practiced by the Banjar community in Indragiri Hilir, Indonesia. While classical interpretations of QS. An-Nisā’ (4):11–12 have predominantly emphasized fixed inheritance ratios, such readings often overlook the ethical objectives (maqāṣid al-sharī‘ah) and relational dimensions embedded within the Qur’anic discourse on family and justice. Drawing on a qualitative case study approach that integrates maqāṣid-based hermeneutics, reciprocal (mubādalah) interpretation, and secondary ethnographic data, this study explores how local deliberative practices function as a living interpretation of the Qur’an. The findings demonstrate that basuluh operates not as a deviation from Qur’anic norms but as a contextual mechanism for realizing justice through mutual consent, responsibility, and family harmony. By foregrounding principles such as ghayra muḍārrin (non-harm), bil-ma‘rūf (recognized fairness), and reciprocal moral responsibility among heirs, the Banjar practice reflects a relational understanding of justice that aligns with the Qur’an’s ethical vision. This study contributes theoretically by advancing a maqāṣidī–reciprocal framework for Qur’anic interpretation, challenging rigid legal formalism while preserving normative integrity. Practically, it offers an alternative model for contextualizing Islamic inheritance law in plural socio-cultural settings without undermining Qur’anic authority